Comparison of GLP-1 analogues versus sitagliptin in the management of type 2 diabetes: systematic review and meta-analysis of head-to-head studies. - Tiansheng Wang; Zhuoyue Gou; Fei Wang; Manling Ma; Suo-di Zhai (PLoS ONE)
Background Incretin-based therapies which include glucagon-like peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors are recommended by several practice guidelines as second-line agents for add-on therapy to metformin in patients with type 2 diabetes (T2DM) who do not achieve glycemic control with metformin plus lifestyle interventions alone. The purpose of this study is to perform a systematic review with meta-analysis of existing head to head studies to compare the efficacy and safety of GLP-1 analogues with DPP-4 inhibitors. Methods We performed a systematic review and meta-analysis of head-to-head studies to compare GLP-1 analogues with DPP-4 inhibitors in the management of type 2 diabetes. A random effects model was selected to perform the meta-analyses, results were expressed as weighted mean differences for continuous outcomes and relative risks for dichotomous outcomes, both with 95% confidence intervals, and with I2 values and P values as markers of heterogeneity. Results Four head-to-head randomized controlled studies with 1755 patients were included. Compared to sitagliptin, GLP-1 analogues are more effective in reducing HbA1C (weight mean difference -0.41%, 95% CI -0.51 to -0.31) and body weight (weight mean difference -1.55 kg, 95% CI -1.98 to -1.12). Conversely, GLP-1 analogues are associated with a higher incidence of gastrointestinal adverse events compared to sitagliptin: nausea (relative risk 3.14, 95% CI 2.15 to 4.59), vomiting (relative risk 2.60, 95% CI 1.48 to 4.56), diarrhea (relative risk 1.82, 95% CI 1.24 to 2.69), and constipation (relative risk 2.50, 95% CI 1.33 to 4.70). Conclusions The result of this meta-analysis demonstrates that compared to sitagliptin, GLP-1 analogues are more effective for glycemic control and weight loss, but have similar efficacy in reducing blood pressure and lipid parameters, however, GLP-1 analogues are associated with a higher incidence of gastrointestinal adverse events and a similar incidence of hypoglycemia compared to sitagliptin.